Integrating disaster management and poverty reduction - Hsu, Claire; Huang, Chengwei (International Food Policy Research Institute, 2016)
In light of the growing theoretical and policy paradigm of integrating disaster reduction and poverty alleviation efforts (World Conference on Natural Disaster Reduction Yokohama 1994; Wisner et al. 2004), China sought to blend risk and vulnerability reduction, disaster mitigation, and poverty alleviation in its short-term recovery program following the Wenchuan earthquake (Dunford and Li 2011). The task of integrating these policy goals, however, remains relatively recent, much remains to be done, and many knowledge gaps remain to be filled (Huang and Li 2012). This chapter introduces the concepts of disaster and poverty, reviews the available literature on their interaction during the Wenchuan earthquake, and recommends ways to better combine these two policy agendas, with community-based disaster management (CBDM) figuring centrally.